WEWE MERENTAS GUNUNG: MITOLOGI MASYARAKAT BESEMAH SUMATERA SELATAN - Sari Herleni (Madah: Jurnal Bahasa dan Sastra, 2015)
This study is based on the assumption that by reading literary works, we can enjoy a culture of a society. By discussing the elements of mythology stories Wewe Merantas Gunung, it is expected to be able to understand what the source of mythology of the story is. It includes four elements of understanding such as the types, characters, functions, and methods of telling the story. The result of the study showed that the source of mythology of the environment of Besemah society itself is hilly. This kind of mythology is a myth that the story is considered really existed by the community, even it is considered to be the taboo matter. The main character is Wewe while the subordinate characters are is the old brother and the middle brother. Mythology has functions as moral controlling and as reminder something and the method of story telling is narrative, the story telling is expressed by the author completely.